Akzeptanz digitaler Apps in der Nachsorge von Patient*innen mit Kopf-Hals-Tumoren - Weusthof, Christopher; Zhu, Zhaojun; Ruck, Anne; Bolooki, Amir; Schöffski, Oliver; Wollenberg, Barbara; Wirth, Markus (HNO, 2024)
Background: Patient-reported outcome (PRO) measures lead to improved quality of life in cancer patients and possibly to earlier detection of tumor recurrence. Objective: Patient interest in complementing tumor follow-up care with apps for recording PROs was assessed using a questionnaire. Materials and methods: An independently created questionnaire to record the interest of tumor patients in a digitalized form of tumor follow-up care was evaluated (n = 110). Results: In the study, the majority of tumor patients were interested in using an app for tumor disease. Taking age into account, the number increased even further for patients < 60 years of age, as expected. In line with this, human papillomavirus (HPV)-positive patients showed significantly greater interest (p = 0.021). Conclusion: The introduction of an app is supported by the majority of tumor patients. In addition to recording PROs, other applications (appointment reminders, patient files, sports/nutrition programs) could also be integrated.
CRIS-Team Scopus Importer:2024-05-10
Keywords: Data collection; Human papilloma virus; Patient-reported outcome measures; Quality of life; Questionnaire